1961
DOI: 10.1152/ajplegacy.1961.201.2.357
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of deuterium on dogs

Abstract: The physiological consequences of the deuterium isotope effect in large mammals were studied in two dogs, one of which was maintained at 20% concentration of D2O in the body fluids for 50 days, and the other at the toxic range of 33–35% for a brief period. Deuteration of the dogs was effected by replacement of ordinary water with deuterium oxide in both food and drink. Hemoglobin, hematocrit, and red blood cell count dropped but the white blood cell count was essentially unaffected although there was a progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 0 publications
2
34
0
1
Order By: Relevance
“…Our data are supported by previous studies with cell cultures, superfused organ cultures, animal experiments, and clinical experience, where no significant toxic effects for lower systemic doses were shown [16][17][18]. They also demonstrated toxicity starting at a 30 % concentration, which exceeds the tested deuterium concentration of 0.13 ml/ml.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our data are supported by previous studies with cell cultures, superfused organ cultures, animal experiments, and clinical experience, where no significant toxic effects for lower systemic doses were shown [16][17][18]. They also demonstrated toxicity starting at a 30 % concentration, which exceeds the tested deuterium concentration of 0.13 ml/ml.…”
Section: Discussionsupporting
confidence: 89%
“…Since most of the toxic effects are centralized in neuronal tissue, toxic effects upon direct contact with the retinal cells are possible. It has been shown that mammals can tolerate a concentration of up to 30 % of D2O in drinking water, and that a short exposure to a blood serum deuterium fraction of up to 0.23 ml/ml seems to be safe [14][15][16][17][18]. The tested concentration in this study is 0.13 ml/ml.…”
Section: Introductionmentioning
confidence: 81%
“…Although not statistically evaluated due to the small sample size, human retinal preparations support these data, showing either a slight increase or a minimal decrease in ERG amplitudes at the end of the washout [37]. Our data are supported by previous studies with cell cultures, superfused organ cultures, animal experiments, and clinical experience, where no significant toxic effects for lower systemic doses were shown [40,41,42]. Toxicity has been detected at a 30% concentration, which exceeds the tested deuterium concentration of 0.13 ml/ml.…”
supporting
confidence: 83%
“…At the outset it is interesting to note that water's seeming ambivalence to quantum effects for some properties is reflected in the fact that prokaryotic organisms such as bacteria can tolerate pure D 2 O conditions (43), while deuterating about 30% of plant's and mammal's water can be lethal (44)(45)(46).…”
Section: Experimental Observations Of Nuclear Quantum Effects In Watermentioning
confidence: 99%